1982
DOI: 10.1002/app.1982.070270126
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of polyester fibers degraded by aminolysis and by alkalin hydrolysis

Abstract: SynopsisPermeant degradation affects the brittleness, flexural fatigue, and .ultimate tensile properties of polyester fibers more drastically than topochemical degradation. Topochemical degradation was obtained by hydrolysis with aqueous NaOH and permeant degradation by aminolysis with aqueous ethylamine. Treatment with aqueous sodium hydroxide appears to leave the polyester fiber surfaces more resistant to abrasion damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
84
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 1 publication
6
84
0
Order By: Relevance
“…Therefore, in this study, cysteine was immobilized on aminolyzed and carboxylated PET to assess the effects of surface modification on polymer properties and to assess the stability of cysteine immobilization. Since polymer properties of hydrolyzed PET were assessed in this study and showed a loss of mechanical strength caused by hydrolysis, which is consistent with previous studies, cysteine immobilization on hydrolyzed PET was not studied [14,15,22,31].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Therefore, in this study, cysteine was immobilized on aminolyzed and carboxylated PET to assess the effects of surface modification on polymer properties and to assess the stability of cysteine immobilization. Since polymer properties of hydrolyzed PET were assessed in this study and showed a loss of mechanical strength caused by hydrolysis, which is consistent with previous studies, cysteine immobilization on hydrolyzed PET was not studied [14,15,22,31].…”
Section: Introductionmentioning
confidence: 55%
“…Also, once the coated NTPDase is washed off, the polymer would lose the hemocompatibility. Studies done by Marconi et al [40] immobilized NTPDase to hydrolyzed PET, despite hydrolyzed PET showing loss of mechanical strength due to hydrolysis [14,15,22,31]. Based on these studies, immobilization of NTPDase to mechanically stable PET would potentially enhance hemocompatibility.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, even in controlled state, the fiber surface is gradually degenerated with the development of the reaction. This condition results in generating holes, weakening the surface and consequently diameter and strength of the fibers reduction after hydrolysis reaction [2,6,7].…”
Section: Introductionmentioning
confidence: 97%
“…Collins et al 20 have analyzed the molecular weight distributions of aminolyzed PET using gel-permeation chromatography. Ellison et al 21 have reported the physical properties of PET fibers degraded by aminolysis, whereas Farrow et al 22 have studied the degradation of PET by methylamine through infrared and X-ray methods. Popoola 23 suggested the aminolytic degradation of PET and mechanism of the reaction.…”
Section: Introductionmentioning
confidence: 98%